MASALAH-MASALAH YANG DIALAMI SISWA MTS NEGERI KAMPAR TIMUR T.P 2015/2016 - Asni '; Rosmawati '; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The study is aimed at 1) finding out the description of personal problems experienced by male and female students; 2) finding out the description of emotional problems experienced by male and female students; 3) finding out the description of learning problems experienced by male and female students; 4) finding out the description of familial problems experienced by male and female students; 5) finding out the description of social problems experienced by male and female students; 6) finding out the description of the problems experienced by male and female students dealing with personal, emotional, learning, familial, and social aspects; 7) finding out the description of overall students' problems. The data dealing with student problem preferences based on personal, emotional, learning, familial, and social aspects were collected by using questionnaire. The subjects of the research are 216 8th Grade students of Kampar Timur State Islamic Junior High School whose choise were based on sex. The sampling technique is the total one. The research results showed that: 1) 70 moderate category male students (67%) and 79 moderate category female students (70%) experienced personal problems namely self confidence. 2) 70 moderate category male students (67%) and 73 moderate category female students (65%) experienced emotional problems namely sadness. 3) 73 moderate category male students (70%) experienced learning motivation and 93 moderate category female students (83%) experienced learning achievement problems. 4) 66 low category male students (63%) and 60 low category female students (54%) experienced familial problems namely relationship with parents. 5) 75 low category male students (72%) experienced social problems namely relationship with teachers and female students and 78 low category female students (70%) experienced social problems namely relationship with peer group. 6) The problems of personal, emotional, learning, familial, and social aspects experienced by male and female students are about learning motivation and they are still in moderate category. 7) In general, the problems experienced by male students and female students which are categorized high are emotional i.e. 16% dealing with sadness.Keywords: Problems of Students